Root canal debridement efficacy of heated sodium hypochlorite in conjunction with passive ultrasonic agitation: An ex vivo study - Yogesh Damade; Ramchandra Kabir; Sunanda Gaddalay; Sharvaree Deshpande; Sonali Gite; Sandip Bambale; Nileshkumar Dubey (Tabriz University of Medical Sciences, 2020)
Background. This study aimed to investigate the endodontic debridement efficacy of different sodium hypochlorite (NaOCl) irrigation regimens with and without ultrasonic agitation, followed by ethylenediaminetetraacetic acid (EDTA) via scanning electron microscopy (SEM) after using a rotary instrumentation system. Methods. Mandibular premolars (n=50) were randomly divided into five experimental groups (n=10) for root canal instrumentation with ProTaper Universal rotary system up to F3. The root canal system was treated with intracanal-heated NaOCl (100°C) or preheated NaOCl (55°C), followed by ultrasonic agitation and EDTA treatment. Samples irrigated with conventional needle irrigation (CNI) using normal saline solution were used as controls. Debridement efficacy was analyzed by SEM. A five-point scale was used to estimate the presence/absence of debris for each canal segment (coronal, middle, and apical). The results were analyzed using one-way ANOVA and post hoc Tukey tests (P<0.05). Results. The experimental groups exhibited less debris compared to CNI with saline (P<0.05). The amount of debris decreased significantly for the group with NaOCl intracanal heating compared to extraoral heating. Ultrasonic agitation further enhanced the root canal debridement efficacy of NaOCl. Conclusion. In summary, intracanal heating of NaOCl with and without ultrasonic agitation followed by EDTA appears to be a promising method to flush debris from the root canal system.